The Relationship Between Green Human Resource Management Activities And Corporate Commitment: An Overview - Thenmozhi, S; Kalaiarasan, C; E. , Nirmala; K. , Bhuvaneswari (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Human Resource Management is an important managerial role that deals with an organization's most valuable asset: its employees. Today, the entire history of HRM is being investigated for its long-term feasibility. To be clear, we all believe that Green Human Resource Management is the most important aspect of long-term sustainability. Green HRM is a form of human resource management that focuses on a company's environmental concerns. Green HRM is described as the application of human resource management policies to encourage the productive use of resources within businesses and to support environmental causes, thus raising employee morale and organisational engagement. The aim of this study was to look at the relationship between green human resource management activities and organisational engagement.